Developing behavioural markers of high-speed workboat crews' competencies. - Lehtimäki, Mikko; Teperi, Anna-Maria (International Journal of Occupational Safety & Ergonomics, 2026)
This study defines the competencies, structured as behavioural markers, that lead to an excellent performance by high-speed workboat crews in cockpit work and can promote maritime safety and operational efficiency. A need to better understand crew performance in cockpit work has been identified in this maritime specialty. The behavioural marker taxonomy is based on aviation standards, further reasoned by human factor models and maritime knowledge. It was formed utilizing content analysis and validated at the prototype level using observation data from actual cockpit work. The tested behavioural markers modelled crew behaviours in eight competency areas. This study contributes to improving crew and operative performances and safety, and to developing socio-technical systems in the field. The study also reveals further research topics for supporting cockpit and bridge crews in safety-critical high-speed maritime environments.